A note on Kakutani type fixed point theorems - A. R. Khan; N. Hussain; L. A. Khan (International Journal of Mathematics and Mathematical Sciences)
We present Kakutani type fixed point theorems for certain semigroups of self maps by relaxing conditions on the underlying set, family of self maps, and the mappings themselves in a locally convex space setting.